2018
DOI: 10.1177/1756286418774267
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in stroke: the role of cholinergic, purinergic and glutamatergic signaling

Abstract: The inflammatory response is a major factor in stroke pathophysiology and contributes to secondary neuronal damage in both acute and chronic stages of the ischemic injury. Recent work in experimental cerebral ischemia has demonstrated the involvement of neurotransmitter signaling in the modulation of neuroinflammation. The present review discusses recent findings on the therapeutic potential and diagnostic perspectives of cholinergic, purinergic and glutamatergic receptors and transporters in experimental stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 111 publications
(204 reference statements)
2
15
0
2
Order By: Relevance
“…Inflammation of the nervous system (termed neuroinflammation) has been shown to play a pivotal role in neurodegenerative diseases such as Alzheimer disease, Parkinson disease, traumatic brain injury, and stroke. 3 5 What has emerged more recently is that diseases that were largely thought to be based on dysregulation of neurotransmitter systems such as mood disorders (including depression and anxiety), schizophrenia, and chronic pain now appear to have neuroinflammation as a key element (reviewed in Skaper et al 4 ).…”
Section: Overview Of Neuroinflammationmentioning
confidence: 99%
“…Inflammation of the nervous system (termed neuroinflammation) has been shown to play a pivotal role in neurodegenerative diseases such as Alzheimer disease, Parkinson disease, traumatic brain injury, and stroke. 3 5 What has emerged more recently is that diseases that were largely thought to be based on dysregulation of neurotransmitter systems such as mood disorders (including depression and anxiety), schizophrenia, and chronic pain now appear to have neuroinflammation as a key element (reviewed in Skaper et al 4 ).…”
Section: Overview Of Neuroinflammationmentioning
confidence: 99%
“…In tandem, there is a cascade of inflammatory pathways upregulating pro-inflammatory cytokine production, all of which in turn activating various cell death signals for necrosis and programed cell death. Of note, recent studies have demonstrated the involvement of neurotransmitter signaling in the modulation of neuroinflammation [ 77 ]. Hence, further studies that investigate the role of the inflammation-associated vasculome and purinergic signaling in ischemic stroke is essential.…”
Section: Discussionmentioning
confidence: 99%
“…158 Several complex cascades of processes in early stroke are influenced by afferent and efferent pathways of the vagus nerve. 159 VNS is a potential tool for subacute stroke recovery owing to its anti-inflammatory and neuromodulators releasing properties. 160,161 Invasive VNS is normally 0.25 to 3 mA, equipped with bipolar electrodes placed underneath the chest skin and the left vagus nerve.…”
Section: Vagus Nerve Stimulationmentioning
confidence: 99%